Design and Analysis of six DOF Robotic Manipulator. Issue 1 (February 2021) - Pratheep, V G; Chinnathambi, M; Priyanka, E B; Ponmurugan, P; Thiagarajan, Pridhar
Abstract: The robotic manipulators are nowadays used for many applications in the industries. This project involves the design and analysis of a six DOF manipulator for welding, pick and place application. We developed a robot in Solid Works and analysed it motion, load withstanding capacity and path traceability. However, design and analysis of a robot involves modelling of it forward and inverse kinematics. We modelled the forward and inverse kinematics by D-H parameters. The proposed model makes it possible to control the manipulator to achieve any reachable position and orientation in an unstructured environment. The inverse kinematics provided many possible combinations of angles for a single end effector position. A GUI was created in MATLAB for studying the forward and inverse kinematics of the robot. It gave results with precision of 0.2 cm. the load analysis also gave the maximum load it can withstand 200 KN without permanent deformation. The approach presented in this work can also be applicable to solve the kinematics problem of other similar kinds of robot manipulators.